Performance analysis : knowing what to do and how - Brethower, Dale M. (HPT in action series, 2007)
Performance Analysis: Knowing What to Do and How. Dale Brethower. In Performance Analysis: Knowing What to Do and How, Dr. Dale Brethower takes a fresh look at finding out what will work to change and improve performance. The book presents a systems thinking approach to improving performance and contains tools for creating interventions that will be implemented, will have a favorable impact and can be maintained and continually improved. In three sections, the author walks you through a process you can follow to:. & bull; Look at performance issues through a systems thinking lens. & bull; Specif.